Connecting Students’ Attitudes Toward Birds with Conservation Attitudes, Beliefs, and Knowledge Regarding the Grey Partridge (Perdix perdix) - Ljubomir Mohorič; Ivan Kos; Vesna Mihelič Oražem; Iztok Tomažič (Animals)
As a farmland species, the grey partridge is facing a drastic decline all over Europe. In Vipava Valley (Slovenia), the species was last observed around 20 years ago. In this region, an initiative for reintroducing grey partridges was put forward, with much effort dedicated to breeding partridges and monitoring breeding success in a closed area. One of the initiative’s goals was to assess the local community’s attitudes, beliefs, and knowledge regarding birds and grey partridges. In this study, we investigated students’ attitudes toward birds in general, their attitudes toward and knowledge of grey partridges, and their beliefs about the feasibility of grey partridge reintroduction. Students generally supported the conservation of birds and grey partridges. However, they were neutral regarding learning about birds and undecided about the success of their reintroduction. Their beliefs regarding partridge reintroduction from the standpoint of natural heritage protection were slightly positive. The results showed that students were not familiar with the species. The study programme, willingness to volunteer, and amount of knowledge showed the most significant effects on students’ attitudes and beliefs. This study indicates that formal education should focus more on informing students about local biodiversity and related issues to raise local community awareness and engage them in conservation actions.